Development of Digital Worksheet Using Online Geogebra to Enhance Geometric Thinking Skills - Hadi, Windia; Mariana, Sri (Supermat : Jurnal Pendidikan Matematika, 2024)
This research is significant in answering the challenges of increasingly sophisticated technology in creating worksheets using Geogebra software. This research aims to produce digital worksheet products using GeoGebra online based on students' geometric thinking levels that are valid and practical to use in teaching and learning processes in the classroom, both online and offline. The research method used in this study is research and development (Research and Development) with the ADDIE model. The ADDIE model has five stages: analysis, design, development, implementation, and eval__uation). The subjects of this research were students of the mathematics education study program for the 2021/2022 academic year. The instruments used were material and media expert validation sheets and student response sheets. The results of this study are digital worksheet products using GeoGebra Online based on students' geometric thinking levels that are valid and practical to use. Digital worksheets using GeoGebra online is an innovative use of technology that integrates student activity sheets.